Effects of Selected Core Stability Exercises on Dialysis Quality and Muscular Strength of Male Hemodialysis Patients - Mehrdad Bastani; Gholamali Ghasemi; Morteza Sadeghi; Vazgen Minasian (Shiraz University of Medical Sciences, 2018)
Background: Hemodialysis patients with end-stage renal disease (ESR) have lower physical, emotional, and cognitive functions than healthy people of the same age due to their inactive lifestyles and treatment approaches. This study aimed to investigate the effects of selected core stability exercises on the dialysis quality and muscular strength of male hemodialysis patients. Methods: In this quasi-experimental study, 30 male hemodialysis patients (age: 62.24±6.51 years; history of dialysis: 9.4±18.44 months) were selected by convenience sampling and assigned into experimental (n=15) and control (n=15) groups. The quality of dialysis and muscular strength of the subjects were assessed by blood sampling before and after dialysis and 5× sit-to-stand tests, respectively. A core stability exercise program was performed for 6 weeks, 3 sessions per week, 45 minute per session. Results: Data analysis showed that there was no significant difference in the quality of dialysis between the experimental and control groups (P=0.485), but a significant difference was observed in muscular strength between the two groups (P=0.001). Exercise has a significant effect on the variable. Conclusion: Based on the results of this study, core stability exercises can be recommended to male hemodialysis patients as a safe and practical strategy for improving their muscular strength and quality of life.